Euro Area Policies : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper discusses the impact of workforce aging on productivity in the euro area. The euro area population has aged considerably over the past few decades, and the process is expected to accelerate in the years ahead. At the same time, labor productivity growth in the euro area has been sluggish, posing risks to long-term growth prospects. It is estimated that workforce aging could significantly retard total factor productivity (TFP) growth over the medium to long term. Given current demographic projections from the Organisation for Economic Co-operation and Development, the aging of the workforce in the euro area could lower TFP growth by about 0.2 percentage points each year between 2014 and 2035. Appropriate policies can, however, mitigate the adverse effects of aging.